Evaluation of Mortality Risk Prediction Using Pediatric Index of Mortality 2 in Pediatric Intensive Care Unit at Chiang Mai University Hospital - Kaphan, Kraiwan; Intaboonma, Sukanlaya; Janamnuay, Warunee; Muangcom, Supanee; Chaisuwan, Chisanucha; Thepyayon, Sommai; Ontakhrai, Patcharaporn; Sarnkhao, Supattra (Biomedical Sciences and Clinical Medicine, 2016)
Objective To validate the performance of Pediatric Index of Mortality 2 (PIM2) and the quality of care in Pediatric Intensive Care Unit (PICU). Methods This is a prospective study conducted in PICU of Chiang Mai University Hospital. One hundred and twenty patients, age from 1 day to 15 years old, admitted to PICU between 2 November 2012 and 31 August 2013, were recruited. The PIM2 scoring system was used. Discrimination power was analyzed by area under the receiver operating characteristic curve (AUC), calibration was analyzed by Hosmer-Lemeshow goodness-of-fi t test. Quality of care in PICU was evaluated by Standardized Mortality Ratio (SMR). Result Fifty eight point four percent of the patients were male and 56.30% were less than 3 years old. Respiratory illness was the most common diagnosis on admission (30.30%). Sixty four point seven percent of this patients received mechanical ventilator support during their stay in PICU. The predicted mortality according to the PIM2 score ranged from 0.01% to 98.57% with a mean of 21.63% and 38 cases (11.87%) died. Discrimination between survival and death assessed by the AUC was 0.80 [95% confidence interval (CI) 0.71-0.87] resulting from the calculation of the PIM2 score 4.05%. Calibration according to the Hosmer-Lemeshow goodness-of-fi t test showed a Chi-square value of 6.40 (df = 2), p = 0.59. The SMR for the whole population was 0.55 (95% CI 0.04–1.06). Conclusion PIM2 showed good discriminatory power and good calibration as well as quality of care of the PICU.